First record of the Cyrtodactylus brevipalmatus group (Squamata: Gekkonidae) from Vietnam with description of a new species - Le, Dzung Trung; Sitthivong, Saly; Tran, Tung Thanh; Grismer, L. Lee; Nguyen, Truong Quang; Le, Minh Duc; Ziegler, Thomas; Luu, Vinh Quang (Zootaxa, 2021)
A new species of the genus Cyrtodactylus is described from Dien Bien Province, northwestern Vietnam based on morphological and molecular data. Cyrtodactylus ngati sp. nov. can be distinguished from remaining congeners by the following combination of characters: maximum SVL 69.3 mm; dorsal pattern consisting of six dark irregular transverse bands between limb insertions; inter-supranasals one; dorsal tubercles present on occiput, body, hind limbs and on first half of tail; 17–22 irregular dorsal tubercle rows at midbody; lateral folds clearly defined, with interspersed tubercles; 32–38 ventral scales between ventrolateral folds; 13 precloacal pores separated by a diastema of 5/5 poreless scales from a series of 7/7 femoral pores in enlarged femoral scales; precloacal and femoral pores absent in females; 1–3 postcloacal tubercles on each side; transversely enlarged median subcaudal scales absent. In the molecular analyses, the new species is shown to be the sister taxon to C. interdigitalis from Thailand. This is the 47th species of the genus Cyrtodactylus and the first member of the C. brevipalmatus species group recorded from Vietnam.